Proteomics for Bioenergy Production - Salvato, Fernanda; Santos, Bruna Marques dos [UNESP]; Santana Costa, Marilia Gabriela de [UNESP]; Gutierrez Rodriguez, Edwin Antonio [UNESP]; DoNascimento, D. D.; Pickering, W. A. (Bentham Science Publ, 2017)
This chapter reviews the importance and application of proteomics tools for studying bioenergy crops and microorganisms employed in sugar fermentation and/or degradation of cell wall compounds. The large volume of information from genome sequencing projects has allowed the development of many new platforms for profiling each step of the genetic information flow from DNA to protein to many molecular interactions involved in phenotype determination. In this context, proteomics is a comprehensive package of tools dedicated to identifying and characterizing protein expression in different biological systems. In this article, the application of proteomics in bioenergy production from feedstock is summarized, citing studies associated with the reduction of lignocellulose biomass recalcitrance and the discovery of more efficient enzymes for cell wall disruption and of potent microorganisms for sugar fermentation.
Keywords: Bioenergy; Biofuel; Biomass; Enzymes; Feedstock; Lignocellulose; Lignin; Maize; Mass spectrometry; Microorganisms; Oil; Proteomics; Proteome; Renewable; Saccharification; Subcellular; Sugarcane; Sorghum; Trees; 2D gel electrophoresis